1997
DOI: 10.1002/(sici)1096-8628(19970822)71:3<298::aid-ajmg10>3.0.co;2-f
|View full text |Cite
|
Sign up to set email alerts
|

Intersitial deletion of 20p: New candidate region for Hirschsprung disease and autism?

Abstract: We describe a patient with Hirschsprung disease and autism. High-resolution karyotyping indicated that the patient has an interstitial deletion of 20p11.22-p11.23. Microsatellite analysis showed a deletion involving a 5-6 cM region from the maternally derived chromosome 20. The deleted region is proximal to, and does not overlap, the recently characterized Alagille syndrome region. This region of 20p has not yet been implicated in Hirschsprung disease or autism. However, this region contains several genes that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 71 publications
1
15
0
Order By: Relevance
“…Among previous identified chromosomal aberrations in HSCR patients, chromosome 10q21.2 and 20p11.22-p11.23 regions 4,6 were confirmed in this study as follows: (1) The LOH frequency of chromosomal 10q21.2 region (including ANK3, ARID5B, C10orf107, CDK1, RHOBTB1, and TMEM26) was higher in HSCR cases (2.4%) than in controls (0.2%) with a nominal association (P 5 0.04, Table III), and (2) a large-scale aberration of chromosomal 20p11.23-p11.21 region appeared unique to HSCR cases (Supplementary Table III). Chromosomal 15q11.2 region, which was identified as a large and rare CNV in another genome-wide copy number analysis for HSCR, 8 was also confirmed to have a lower frequency of CNV in the HSCR case group (0.8%, P 5 0.04) than in the control group (5.1%), as shown in Table II.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Among previous identified chromosomal aberrations in HSCR patients, chromosome 10q21.2 and 20p11.22-p11.23 regions 4,6 were confirmed in this study as follows: (1) The LOH frequency of chromosomal 10q21.2 region (including ANK3, ARID5B, C10orf107, CDK1, RHOBTB1, and TMEM26) was higher in HSCR cases (2.4%) than in controls (0.2%) with a nominal association (P 5 0.04, Table III), and (2) a large-scale aberration of chromosomal 20p11.23-p11.21 region appeared unique to HSCR cases (Supplementary Table III). Chromosomal 15q11.2 region, which was identified as a large and rare CNV in another genome-wide copy number analysis for HSCR, 8 was also confirmed to have a lower frequency of CNV in the HSCR case group (0.8%, P 5 0.04) than in the control group (5.1%), as shown in Table II.…”
Section: Discussionsupporting
confidence: 76%
“…2 Previous studies have identified several chromosomal aberrations (e.g., 2q22, 10q11.2/q21.2, distal 13q, 20p11.22-p11.23) associated with HSCR. [3][4][5][6] In addition, a recent study examined 67 HSCR-related markers, including 11 previously known neuro-developmental genes, and identified copy number variants (CNVs) at 3 loci of MAPK10, ZFHX1B, and SOX2. 7 Even more recently, a genome-wide copy number analysis in a Chinese population discovered neuregulin 3 (NRG3), located on 10q23.1, to be a contributing structural variant.…”
Section: Introductionmentioning
confidence: 99%
“…According our results using the same data set, this linkage is supported by paternal transmission. Deletions of the 20pter region have been reported in two distinct autism cases [41], [42]. The first patient presented an interstitial deletion in 20p11.22-p11.23 whereas the second, a 3-year-old boy with a moderate to severe mental retardation and autistic behavior patterns, carried a deletion at 20pter-p12.2.…”
Section: Resultsmentioning
confidence: 99%
“…Deletions of the short arm of chromosome 20 are a relatively rare chromosome abnormality, with less than 35 such patients reported in the literature (Anad, et al, 1990; Byrne, et al, 1986; Dutta, et al, 1991; Garcia-Cruz, et al, 1985; Garcia-Heras, et al, 2005; Kiss and Osztovics, 1988; Krantz, et al, 1997; Laufer-Cahana, et al, 2002; Legius, et al, 1990; Li, et al, 1996; Michaelis, et al, 1997; Oda, et al, 2000; Rand, et al, 1995; Rovet, et al, 1995; Sauter, et al, 2003; Schnittger, et al, 1989; Shohat, et al, 1991; Silengo, et al, 1988; Spinner, et al, 1994; Teebi, et al, 1992; Zhang, et al, 1990). The observation that multiple patients with deletions of 20p12 had the autosomal dominant disorder Alagille syndrome (AGS; MIM# 118450), led to the positional cloning of the AGS disease gene, Jagged1 ( JAG1 ; MIM# 601920) (Li, et al, 1997; Oda, et al, 1997).…”
Section: Introductionmentioning
confidence: 99%